Local Government Policies in Handling Domestic Violence (KDRT) During Pandemic COVID-19 - Didin Muhafidin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Corona Virus Disease 2019 or better known as COVID-19, has hit all countries in the world. It can be said that this pandemic is a human tragedy since a lot of people suffer and are seriously ill. The global economy and social institutions are struggling, which adds to totalitarian and oppressive regimes in many nations. In the household sector, COVID-19 has caused vulnerability to family resilience, where the pandemic of a family head has lost his job and income, which impacts the family economy. This will cause various further impacts, such as disharmony, leading to Domestic Violence (KDRT). Therefore, the government needs to make a policy breakthrough in dealing with Domestic Violence (KDRT). Therefore this study aims to discuss government policies, especially local governments, in handling domestic violence due to the COVID-19 pandemic. This study uses a qualitative approach with descriptive methods to provide an overview of the object studied. The results showed that domestic violence increased along with the development of the COVID-19 pandemic. Law No. 23 of 2004 concerning the elimination of domestic violence is not capable of being the only way to deal with these acts of domestic violence. This is due to the implementation that is not running optimally because several regions have high patriarchal culture and have regional policies that contradict the law. This research also encourages local governments to make a policy that involves third parties such as NGOs and organizations dealing with discrimination against women and children. This policy can be more pro-domestic violence victims while being monitored with protocols that apply during the COVID -19 pandemic of this.